Debinding process of co-powder injection molded (2C-PIM) SS17-4PH and SS316L - Najlaa Nazihah Mas’ood,; Abu Bakar Sulong,; Norhamidi Muhamad,; Farhana Mohd Foudzi,; Intan Fadhlina Mohamed,; Al-Furjan M.S.H, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Co-Injection Molding Process (2C-PIM) is the extension of powder injection molding (PIM) process which is widely used in manufacturing industry. However, due to two materials being injected, the development of required parts by 2C-PIM can be challenging. Yet, there are many researches that have been done by 2C-PIM process because the process is capable of combining metal-metal, ceramics-metal and ceramics-ceramics. The selections and combinations of materials are depending on the targeted applications. The 2C-PIM process has 4 main processes which are mixing, injection, debinding and sintering. In this paper, SS17-4PH and SS316L were used to conduct the 2C-PIM process. Both materials were mixed with the binder system which is 60 wt.% of palm stearin (PS) and 40 wt.% of polyethylene (PE) to produce as feedstock. The green parts of SS17-4PH and SS316L were prepared by co-injection process. The co-debinding process for these green parts was investigated. Such process was divided into two stages: solvent debinding and thermal debinding. Solvent debinding was conducted with heptane solution at 60 °C. Meanwhile, thermal debinding was conducted at 500 °C for 1 hour holding time and continued with sintering process in the same furnace at 1250 °C. It was found that the binders were 95% removed during solvent co-debinding and such finding is adequate for the co-sintering process based on PIM concept. The co-sintered part was successfully produced and the physical properties of the co-sintered part was observed in order to ensure the bonding is good. Result of SEM image has proved that the co-sintered part of SS17-4PH/SS316L is well bonded.